KNOWLEDGE MANAGEMENT INFRASTRUCTURE AND INNOVATION: INDIRECT EFFECTS OF KNOWLEDGE MANAGEMENT CAPABILITIES AND RESOURCE COMMITMENT - Nasir Mehmood, Muhammad Ashfaq, Sobia Irum (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The knowledge management (KM) is emerging as one of the rising issues and prominent phenomenon in higher education sector of Pakistan. This study aims to examine the effect of knowledge management infrastructure (KMI) on innovation (INN), using mediating and moderating approach in education sector of Pakistan. Present study used convenience sampling technique with a sample size of 235 faculty members. Data was collected through questionnaire and analyzed through Structural Equation Modelling (SEM) technique using Smart PLS software. Findings of this study indicate that KMI has a significant positive relationship with KMC and INN. Moreover, mediation role of KMC on relationship between of KMI and INN and moderation role of resource commitment (RC) on the relationship existing between KMI and KMC were also supported by the results. Findings of this study empirically contributes to the existing KM literature by investigating the actual role of KMI & RC, by reporting high influence of KMI on INN in higher education institutions and by providing valuable insights to establish the strong KMI in order to enhance innovation processes